Prevalence of Burnout Syndrome and its Association with Job Title and Violence among Physicians in Baghdad: A Triangulated Methodology Study - Mohammed, May Abdullah; Ali, Muna Atallah Khaleefah; Marzook, Ahmad Abed; Albayaty, Mohammed (AL-Kindy College Medical Journal, 2023)
Background: Economic Globalization affects work condition by increasing work stress. Chronic work stress ended with burnout syndrome.Objectives: To estimate the prevalence of burnout syndrome and the association of job title, and violence with it among physicians in Baghdad, and to assess the burnout syndrome at patient and work levels by structured interviews.Subjects and Methods: A cross section study was conducted on Physicians in Baghdad. Sampling was a multistage, stratified sampling to control the confounders in the design phase. A mixed qualitative and quantitative approach (triangulation) was used. Quantitative method used self-administered questionnaires of Maslach Burn out Inventory. Qualitative approach used an open-ended question modified from Copenhagen Burnout Inventory by face-to-face interviews. An ordinal logistic regression used in the analysis phase to overcome confounders.Results: The percentages of emotional exhaustion, depersonalization, and feeling of inefficacy were 72.5%, 31.9%, and 12.7% respectively. Total burnout syndrome was 56.4%. Being single and hospital workers were significantly associated with emotional exhaustion (p=0.006, 0.001 respectively) and total burnout syndrome (p=0.017, 0.016 in sequence). In addition to emotional exhaustion and burnout syndrome, singles suffered from depersonalization (p=0.010). Administrative responsibilities made physicians less liable for emotional exhaustion but more prone to feeling of inefficacy (p=0.038, 0.017 respectively).  Less than 40-year age group had a relation with depersonalization, p=0.003, and total burnout syndrome p=0.013. Being male was significant with total burnout syndrome, p=0.008. All Violence types were associated significantly with burnout syndrome and its dimensions, p=0.001 (except feeling of inefficacy in which only threat was significant with it, p=0.054).In qualitative part, the response rate was 80%. It was formulated from 3 themes. Highest percentages in these themes were gained by female and graded physicians.Conclusion: Burnout affects over half of Baghdad’s doctor. Violence was significant to burnout syndrome but job title was not. In qualitative part female and graded physicians were most groups to be affected.